Item Response Theory Analysis of National Intimate Partner And Sexual Violence Survey Measures, (United States), 2010 - Rosay, Andre B. ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This is a secondary data analysis of the 2010 National Intimate Partner and Sexual Violence Survey (ICPSR 36140). The National Intimate Partner and Sexual Violence Survey (NISVS) includes lifetime and past-year measures of physical violence by intimate partners and sexual violence. This secondary data analysis focused on eight measures of physical violence by intimate partners and eight measures of sexual violence. The collection contains 2 SPSS data files: lifetime-data.sav (n=16,507; 22 variables), which measures occurrences of physical and sexual violence over the respondent's lifetime, and pastyr-data.sav (n=4,150; 22 variables), which measure occurrences of physical and sexual violence over the past year. A syntax file is included in the user guide.